Whole blood transcriptome analysis of lactating Murrah buffaloes divergent to contrasting genetic merits for milk yield - Sikka, Poonam; Singh, Kunwar Pal; Singh, Inderjeet; Mishra, Dwijesh Chandra; Paul, Shyam Sundar; Balhara, Ashok K.; Andonissamy, Jerome; Chaturvedi, Krishna Kumar; Rao, Atmakuri Ramakrishna; Rai, Anil (Frontiers in Animal Science, 2023)
Functional genome profiling for milk volume trait was performed through whole blood transcriptome comparing RNA-seq data assembled from high and low milk producing multiparous (5–6 parity) Murrah buffaloes (Bubalus bubalis). Production performance of these buffaloes was the projection of the genetic merit inherited as daughters born to extreme high and low-end bulls ranked for estimated breeding value (EBV) over 150 evaluated bulls under progeny testing scheme. Average (av,) standard milk yield (SMY), i.e. av. 305 days milk yield over the parity of high and low performance buffaloes was recorded as 2909.50 L±492.63 and 1869.57±189.36 L, respectively. Replicates selected within each category of high and low genetic merit showed correlation coefficient of high order (R20,98) while compared with the ‘reference’ assembly assembled from transcriptome libraries of buffaloes (n=16) selected from different physiological state. High and low milk production performing buffalo sequence data, mapped over the Mediterranean water buffalo genome, determined differentially expressed genes (DEGs) depicted through distinct heat maps and volcano plots obtained for two category of animals showing more than 25,000 genes determined through Cufflink analysis. Significant (p<0.05, FDR<0.05) DEGs included 83 downregulating and 142 up-regulating genes. Functional classification of the DEGs revealed a fine networking of biological processes, primarily the cell signaling, cell proliferation, cell differentiation, RNA splicing, fat metabolism and inflammasomes generation in response to infecting agents regulated by transcription factors and binding proteins. TNF alpha signaling pathway, NF-kappa B (NF-κB) signaling pathway and MAPK PI3K-AKT signaling cascade emerged mainly as biological pathways revealing remarkable intricate tuning of metabolic, and cellular processes converging into milk production in buffaloes. Segregated expression patterns obtained for selectively genotyped high and low-milk-yielding Murrah buffaloes using non-invasive method of whole-blood transcriptome revealed gene network and protein–protein interactions involved in lactation. Functioning of transcription factors (TF) and binding proteins in appropriate ambiance of epigenetic regulation, both at post-transcriptional and translational levels consequent upon series of different mammary development stages are the key points in mammogenic and lactogenic responses in subsequent milk secretion under optimum feeding management. These findings may help improve breeding strategies to achieve desired expression of milk yield trait in Murrah buffaloes.